Goldra: premier gisement karstique en Algarve, faune et industries - Antunes, M. Telles (2008)
A bone breccia from Goldra, near Loulé, is studied. It corresponds to the infilling of a karst depression, consisting of: rather worn and probably transported dolomite pebbles at the bottom; accumulations of frequently burnt bone scraps, much broken and with acute edges (no transport), certainly debris of human food, suggesting habitat level (s); in association with the former, stone (flint, quartz, quartzite, graywacke) rather uncharacteristic artifacts that seem compatible with middle and upper Paleolithic, or with Epipaleolithic; and small mammal teeth and bones. Fauna includes an extinct species, Microtus brecciensis recognized for the first time in Portugal. It is not older than Riss-Wiirm interglacial, and may be of this age or later, maybe that of one of wurm's first interstades. Fauna points out to a varied landscape with open country and woods; and to a rather warm and dry temperate, or dry subtropical mediterranean climate. Climate differences should not be significant in comparison with the extant situation. The presence of the mammal species found so far is consistent with modern distribution.